Temples for Cahokia Lords : Preston Holder's 1955-1956 excavations of Kunnemann Mound - Pauketat, Timothy R. (Memoirs of the Museum of Anthropology, University of Michigan, 1993)
"Holder, a brilliant iconoclast, excavated these mounds in 1955 and the excavation still stands 35 years later as one of the best-documented major excavations of the Cahokia area. Unfortunately, he never completed the project. Meticulously researched and written, Pauketat wrote the book Holder never completed, but this volume also reflects the massive research and theoretical developments that have emerged since 1957"--